Assessing child welfare under the Human Fertilisation and Embryology Act 2008: a case study in medicalisation?. Issue 4 (4th January 2014) - Lee, Ellie; Macvarish, Jan; Sheldon, Sally
Abstract This article reports on a study with staff working in assisted conception clinics in the UK about making welfare of the child (WOC) assessments pre‐conception. This aspect of infertility treatment is obligatory under section 13(5) of the Human Fertilisation and Embryology Act, which was amended in 2008. The aim of the study was to find out how this change to the law had impacted on practice. In describing what we found, we also make a contribution to scholarship about the medicalisation of reproduction. S13(5) has often been discussed as a prime example of medicalisation, giving clinics power to grant or deny access to treatment on child welfare grounds, encompassing far more than purely clinical considerations. Yet, while such medicalisation may be entrenched in the law, our findings suggest this power is used with a very light touch. Further, while our interviewees offered near‐universal support for the need to consider child welfare, this is now justified by concerns that address not only family form (e.g. the need for a father figure) but also the quality of interactions between parents and children. In this light we suggest that the concept of medicalisation may offer a rather blunt tool for understanding a far more complex reality.